Pengaruh Beban Kerja Dan Stres Terhadap Kinerja Dan Kesejahteraan Mental Advokat : Studi Kasus Kantor Hukum Advokat Kota Kisaran Barat Kabupaten Asahan - Sundari, Andri Nurwandri, Dewi Atikah, Napsiah Saragih, Rifka Amanda, (CV. PUSDIKRA MITRA JAYA, 2024)
Advocate performance is defined as the effectiveness of services provided by advocates and the efficiency of resources allocated and used to provide these services. There are several things that become obstacles for advocates in resolving cases, and there are certain burdens experienced by advocates. It is clear that becoming an advocate can be said to be easy or not easy, it all depends on the individual advocate. The aim of this research is to find out what influences workload and how to overcome this performance burden. This type of research is descriptive qualitative research using field research methods (empirical), namely research activities carried out at certain Advocates' homes. The data collection methods used by the author in this research were interviews, observation and documentation.